ANDALIMAN QUERCETIN (ZANTHOXYLUM ACANTHOPODIUM DC.) USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) METHOD AND ITS ANTIFUNGAL ACTIVITY AGAINST PITYROSPORUM OVALE - siska, Fitri; Anisa Maharani (Jurnal FARMASIMED (JFM), 2023)
People today complain with dandruff accompanied by itching will cause a lack of confidence because of the unpleasant smell and reduce the beauty of the hair. Andaliman is a plant that grows a lot in the Toba Samosir area which is usually used as a spice for cooking. Examination of secondary metabolite compounds contained in these natural materials is the main thing that is important to do. In other studies, andaliman has been studied to provide antimicrobial, antioxidant, and anti-inflammatory effects. The test method is carried out using the High Performance Liquid Chromatography (HPLC) Method and the minimum inhibitory concentration test using the diffusion method in order to use paper backups with several variations in test concentration. This is related to the content of secondary metabolites such as flavonoids, terpene alkaloids, benzophenthridine alkaloids, pyranoquinoline alkaloids, quaternary isoquinoline alkaloids, aporphyrine alkaloids, essential oils and several types of lignin. Flavonoids are secondary metabolites of polyphenols found in many plants and have a variety of biological effects including antiviral, anti-inflammatory, and antioxidant. Quercetin to derivative active compounds The test results of the minimum inhibitory concentration of the extract showed an average inhibitory power of 17.26 mm at a concentration of 80% and EEAD quercetin levels with a concentration of 6.25; 12,5; 25; 50; and 100 ?g/ml contains quercetin percentages of 143.5, 242.15, 395.12, 865.2, and 1134.12 ?g/ml.